Andragogy and Edutainment Approach: A Cross-Generational Solution for Improved Worship Practices - Slamet Riyadi; Rifal Efendi; Giandra Oliver; Cahya Trismawan; Zuffy Aslam; Muhammad Madjid Wicaksono; Al Kautsar Amin (As-sunnah: Jurnal Pengabdian Masyarakat, 2024)
This research is a Participatory Action Research (PAR) that aims to improve the understanding and practice of ibadah in the Kampung Batu Dalam, Solok district community. Research is carried out through several cycles of planning, action, observation, and reflection. In Cycle 1, diagnosis of problems is carried out through initial observation, identification of problems, analysis of root problems, and consultation with stakeholders. The lecture and learning methods were chosen as the initial action. Cycle 2 focuses on religious learning activities such as worship, sanctification, and sacrament and is taught to the community and children. The methods used include routine learning, competition, and active involvement of the community and children. Evaluations at Cycle 3 show success in raising children's spirits, but the main challenge is the difficulty of reaching older people who are still tied to the old tradition. The main findings of this study were the importance of combining an andragogic approach for the elderly and innovative game-based learning methods for children. Combining these two approaches is a creative and replicable solution to address similar problems in other societies with different characteristics.